Curvature-regulated lipid membrane softening of nano-vesicles. (February 2021) - Chng, Choon-Peng; Sadovsky, Yoel; Hsia, K. Jimmy; Huang, Changjin
Abstract: The physico-mechanical properties of nanoscale lipid vesicles (e.g., natural nano-vesicles and artificial nano-liposomes) dictate their interaction with biological systems. Understanding the interplay between vesicle size and stiffness is critical to both the understanding of the biological functions of natural nano-vesicles and the optimization of nano-vesicle-based diagnostics and therapeutics. It has been predicted that, when vesicle size is comparable to its membrane thickness, the effective bending stiffness of the vesicle increases dramatically due to both the entropic effect as a result of reduced thermal undulation and the nonlinear curvature elasticity effect. Through systematic molecular dynamics simulations, we show that the vesicle membrane thins and softens with the decrease in vesicle size, which effectively counteracts the stiffening effects as already mentioned. Our simulations indicate that the softening of nano-vesicles results from a change in the bilayer's interior structure – a decrease in lipid packing order – as the membrane curvature increases. Our work thus leads to a more complete physical framework to understand the physico-mechanical properties of nanoscale lipid vesicles, paving the way to further advances in the biophysics of nano-vesicles and their biomedical applications.